Ex-vivo Mechanical Testing of Novel Laryngeal Clamps Used for Laryngeal Advancement Constructs - Grzeskowiak, Remigiusz M.; Schumacher, James; Mulon, Pierre-Yves; Steiner, Richard C.; Cassone, Lynne; Anderson, David E. (Frontiers in Veterinary Science, 2020)
Rostral laryngeal advancement, also known as laryngeal tie-forward, is used to treat horses for intermittent dorsal displacement of the soft palate and has a morbidity rate of about 6%. We hypothesized that a novel laryngeal clamp would prevent morbidity associated with the sutures tearing through the thyroid cartilage. Larynges (n = 35 horses) were used for ex vivo testing. For uniaxial testing, 15 equine larynges were tested in one of three laryngeal tie-forward constructs [standard laryngeal tie-forward; modified laryngeal tie-forward using a suture-button; and modified laryngeal tie-forward using a laryngeal clamp]. For biaxial testing, 20 larynges were tested in one of two treatment groups: laryngeal tie-forward and laryngeal tie-forward using a laryngeal clamp. Constructs were tested in single cycle-to-failure. Statistical analyses were performed using ANOVA for uniaxial testing and t-tests for biaxial testing. The laryngeal tie-forward using a laryngeal clamp construct was superior to laryngeal tie-forward and laryngeal tie-forward using a suture-button constructs in resistance to pullout in uniaxial testing. The laryngeal tie-forward using a laryngeal clamp presented a significantly different method of failure than the standard laryngeal tie-forward in the biaxial testing. Failure modes for each construct were primarily by suture failure at the clamp (laryngeal tie-forward using a laryngeal clamp), suture pullout through the thyroid cartilage, or, less commonly, tearing of the cricothyroid ligament (laryngeal tie-forward). In uniaxial testing, the laryngeal tie-forward using a laryngeal clamp failed most commonly due to tearing of the cricothyroid ligament, whereas the standard laryngeal tie-forward and the laryngeal tie-forward using a suture-button failed due to the tearing of the cartilage. The laryngeal clamps provided greater stiffness, load at yield, and tensile stress at yield than did the standard construct. Laryngeal clamps may offer an alternative to standard methods of anchoring the thyroid cartilage when performing the laryngeal tie-forward procedure. Further testing and clinical trials are needed to elucidate the utility of the laryngeal tie-forward using a laryngeal clamp.